Respuestas
Respuesta dada por:
3
(x - 5) * (x - 5) = 144
x² - 10x + 25 = 144
x² - 10x - 119 = 0
Fórmula general de resolución de ecuaciones de 2º grado:
![x = \frac{-b +- \sqrt{b^2 - 4*(a*c)} }{2a} x = \frac{-b +- \sqrt{b^2 - 4*(a*c)} }{2a}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B-b+%2B-+%5Csqrt%7Bb%5E2+-+4%2A%28a%2Ac%29%7D+%7D%7B2a%7D)
![x = \frac{10 +- \sqrt{100+476} }{2} x = \frac{10 +- \sqrt{100+476} }{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B10+%2B-+%5Csqrt%7B100%2B476%7D+%7D%7B2%7D+)
![x = \frac{10 +- \sqrt{576} }{2} x = \frac{10 +- \sqrt{576} }{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B10+%2B-+%5Csqrt%7B576%7D+%7D%7B2%7D+)
![x = \frac{10 +- 24 }{2} x = \frac{10 +- 24 }{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B10+%2B-+24+%7D%7B2%7D+)
x₁ = (10 + 24) : 2 = 34 : 2 = 17
x₂ = (10 - 24) : 2 = -14 : 2 = -7
x² - 10x + 25 = 144
x² - 10x - 119 = 0
Fórmula general de resolución de ecuaciones de 2º grado:
x₁ = (10 + 24) : 2 = 34 : 2 = 17
x₂ = (10 - 24) : 2 = -14 : 2 = -7
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años